Prognostic Significance of the Preoperative Lymphocyte to Monocyte Ratio in Patients With Stage I Non-Small Cell Lung Cancer Undergoing Complete Resection. (13th September 2016) - Xia, Honggang; Sun, Zhongyi; Deng, Limin; Zhu, Deqing; Wang, Dongbin
ABSTRACT: In this study, we investigated the correlation between lymphocyte to monocyte ratio (LMR) and clinical outcomes in stage I non-small cell lung cancer (NSCLC) patients. A total of 439 stage I NSCLC patients were enrolled in this study. Multivariate analyses identified LMR as an independent prognostic factor for recurrence-free survival and overall survival (hazard ratio (HR: 0.469, 95% Confidence Interval (CI): 0.325–0.677, and p < 0.001, and HR: 0.478, 95% CI: 0.332–0.688, and p < 0.001; respectively). Compared with the high LMR group, the proportion of patients who developed distant metastasis was significantly higher in the low LMR group.